Trauma em idosos atendidos pelo serviço pré-hospitalar móvel - Silva, Hilderjane Carla da (2013)
O The aim of this study was to characterize the occurrence of trauma in the elderly population served by the mobile pre-hospital service, in Natal, Rio Grande do Norte. This is a descriptive, transversal and quantitative approach and whose population consisted of 2,080 trauma victims. The sample, of systematic random type, consisted of 400 elderly people, aged from 60 years old, assisted by the Office of Mobile Emergency in Natal / RN, between January 2011 and December 2012. Data collection began after consent and assent of the institution of a Research Ethics Committee under No. 309 505. It was proceeded to documentary retrospective analysis of records of this service through a form of self-development, validated by expert judges considered reliable (α> 0.75) and valid (CVI = 0.97) in their clarity and relevance. Data were tabulated by the Statistical Package for Social Sciences, version 20.0. The results show that older victims have an average age of 74.19 years old, with a prevalence of female involvement by chronic diseases, especially hypertension, average usage of 2.2 routine medications with vital signs within normal limits. The trauma prevailed during the daytime, in the residence of the victims, north of the city and on weekends. Among the mechanisms of trauma were falls, traffic accidents and physical aggression, whose most common type was brain-cerebral trauma and the main consequences were suture wounds and closed fractures. Basic Support Units were as more driven to pre-hospital care (87.8%) and the main destination place consisted of a referral hospital for emergency of the state (57.5%). Among the most commonly performed procedures by nursing staff immobilization with rigid board and neck collar and the peripheral venipuncture, and the main component used for volume replacement to saline were highlighted. There was a significant relationship between the deaths and the mechanism of injury, mechanism of injury and procedures, except medication administration procedures carried out, except immobilization and unit for service. It is highlighted the prevalence of trauma in the elderly, poor follow-up Pre-Hospital Trauma Life Support protocol and the paucity of records and nursing procedures performed. There is need for a protocol of care specific to elderly trauma victims and education strategies for the prevention of such events